Navigating Through Guts: A Comparative Study on COVID-19 and Amebiasis in Children - Khdair Ahmad, Fareed; Jaber, Areej H; Alkurdi, Alaa; Hudali, Hiba; Ibrahim, Sarah; Al-Tarawneh, Lubna A.; Abu Nasrieh, Dima; Bani Hani, Haneen; Dabbah, Yazan Ahmad; Al-Soudi, Mohammad (Jordan Medical Journal, 2025)
Background and Aims: The coronavirus disease 2019 (COVID-19) has global significance with a notable impact on pediatric populations, exhibiting not only respiratory but also gastrointestinal (GI) symptoms. Given that the prevalence of Entamoeba histolytica causing amebiasis in Jordan is 27.8% of annual diarrheal illnesses, our study aimed to delineate the clinical features of COVID-19 in children with a focus on GI manifestations, and to compare these features with those of amebiasis-associated diarrhea. Materials and Methods: We conducted a retrospective cross-sectional analysis at Jordan University Hospital between September and December 2020. The study cohort included children under 18 years with a confirmed diagnosis of COVID-19, assessed for GI symptoms and compared against age-matched controls hospitalized with diarrhea but negative for COVID-19. We evaluated demographic data, clinical presentations, laboratory findings, and outcomes to differentiate between COVID-19 associated diarrhea (CAD) and amebiasis associated diarrhea (AAD). Results: The study included 229 pediatric patients, with 25 hospitalized cases. Among these hospitalized children, 76% exhibited diarrhea, with 21% having concurrent amebiasis. There was no significant age difference between the CAD and AAD groups. Notably, vomiting and abdominal pain were more prevalent in the CAD group, although this did not translate to longer hospital stays. Furthermore, the incidence rates of amebiasis in COVID-19 positive children did not significantly differ from the control group, indicating no exacerbation of amebiasis by COVID-19. Conclusions: Our findings suggested that while GI symptoms were prevalent among pediatric COVID-19 cases in Jordan, the clinical course of CAD appears comparable to that of AAD, without increased severity or prolonged hospitalization. However, it is important to note that the study size was small, which may limit the generalizability of our results This study underscored the importance of considering concurrent etiologies in children presenting with diarrhea during the COVID-19 pandemic and provided a foundational comparative analysis for future research on GI manifestations in pediatric infectious diseases. Further studies with larger sample sizes are needed to validate these findings and explore the full spectrum of GI symptoms in this population.